Conductive glass and preparation method thereof
By punching holes and filling silica on the surface of the conductive glass, easy sublimation compounds are generated and sublimated to form regular air pockets, the problem of insufficient light absorption capacity of TCO conductive glass is solved and its light absorption capacity is significantly improved.
Patent Information
- Application Number
- CN202510066944.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
AI Technical Summary
The light absorption capacity of TCO conductive glass is difficult to further increase, limiting its application in solar cells and other fields.
Pore-like grooves are formed by punching holes on the surface of the glass, filling silica and forming a sublimated compound by plasma etching, which is then sublimated by radiation heating and discharged through perforations, and finally covering the third coating to seal the perforations, forming a conductive glass with regular air pockets.
By preparing regular-shaped air pockets in the conductive coating, the reflection and absorption of light when passing through the conductive glass is increased, and the light absorption capacity of the conductive glass is effectively improved.
Smart Images

Figure CN119874210A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive glass manufacturing, in particular to conductive glass and a preparation method thereof. Background Art
[0002] TCO (Transparent Conductive Oxides) glass, or transparent conductive oxide coated glass, is a transparent conductive oxide film (TCO film) uniformly coated on the surface of flat glass by physical or chemical coating methods. The film materials mainly include oxides of indium (In), antimony (Sb), zinc (Zn) and cadmium (Cd) and their composite multi-element oxides. TCO film is a semiconductor optoelectronic material that increases the number of carriers by doping and other means, so that the system presents degenerate characteristics. Due to its excellent optoelectronic properties such as wide bandgap, low resistivity, high light transmittance in the visible light region and high light reflectivity in the infrared spectrum region, it has long been widely used in solar cells, flat panel displays, organic light-emitting diodes, low-emissivity glass, special function window coatings, transparent thin film transistors and flexible electronic devices.
[0003] TCO conductive glass has good conductive and optical properties, and can increase the light absorption capacity of the semiconductor layer of thin-film batteries. However, its light absorption capacity is difficult to further increase. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing conductive glass and conductive glass, so as to further increase the light absorption capacity thereof.
[0005] In order to solve the above technical problems, the present invention provides a method for preparing conductive glass, comprising the following steps:
[0006] S1, drilling holes on the surface of the glass so that a plurality of hole-shaped grooves are distributed on the surface to obtain a glass substrate;
[0007] S2, preparing a first coating on the glass substrate so that the first coating covers the surface of the hole-shaped groove,
[0008] S3, filling the porous groove with silicon dioxide, wherein the surface of the silicon dioxide after filling is lower than or equal to the hole height of the porous groove;
[0009] S4, using a plasma etching process to make the filled SiO2 react to generate a compound that is easily sublimated;
[0010] S5, continuing to prepare a second coating on the surface thereof to cover the surface of the filled silicon dioxide and the first coating;
[0011] S6, perforating the second coating layer at the hole-shaped groove, wherein the aperture of the perforation is 10-20 nm;
[0012] S7, sublimating the compound in the porous groove by radiation heating and discharging the compound through the perforation,
[0013] S8, continuing to prepare a third coating on the surface thereof to cover the surface of the second coating and seal the perforation;
[0014] Conductive glass with regularly shaped air pockets can be obtained.
[0015] Optionally, in S1, holes are drilled on the surface of the glass by using laser drilling, chemical etching or laser-induced micro-hole deep etching process.
[0016] Optionally, in S1, the hole-shaped grooves are arranged in a uniform array, the depth of the hole-shaped grooves is 1-30 μm, the diameter of the hole-shaped grooves is 0.2-20 μm, and the spacing between adjacent hole-shaped grooves is 5-100 μm.
[0017] Optionally, the first coating, the second coating and the third coating are all transparent conductive oxide coatings (TCO); when preparing the first coating, the second coating and the third coating, physical vapor deposition (PVD) or chemical vapor deposition (CVD) is adopted.
[0018] Optionally, the thickness of the first coating layer is less than half of the diameter of the hole-shaped groove.
[0019] Optionally, the first coating has a thickness of 30-150 nm.
[0020] Optionally, in S3, filling with silicon dioxide specifically comprises the following steps:
[0021] Primary filling: Fill the first dose of silicon dioxide into the porous groove.
[0022] High temperature densification: densification is carried out at a temperature of 900-1100°C for 5-10 minutes.
[0023] Secondary filling: filling the hole-shaped groove with a second dose of silicon dioxide;
[0024] Among them, the ratio of the first dose to the second dose is 1:0.4~0.6.
[0025] Optionally, in S4, the plasma etching process is a Siconi process, which includes the following steps:
[0026] Placing a glass substrate in a SiCoNi process chamber;
[0027] An etching gas is introduced into the process chamber, wherein the etching gas is a mixed gas of nitrogen trifluoride and ammonia.
[0028] The etching gas generates remote plasma under the action of the radio frequency system, reacts with SiO2 to generate a compound that is easily sublimated;
[0029] Optionally, in S7, the temperature of the radiation heating is 170-190°C.
[0030] Optionally, in S6, micro-nano processing technology is used for perforation, and the micro-nano processing technology is any one of electron beam exposure, focused ion beam or nanoimprinting process.
[0031] The present invention also provides a conductive glass, which is made by the above-mentioned preparation method and has a plurality of regularly shaped air pockets in the coating on its surface.
[0032] The present invention provides a method for preparing a conductive glass and the conductive glass. By preparing air pockets of regular shape, uniform size and controllable position in a conductive coating, when light passes through the conductive coating of the conductive glass, the inner wall of the air pocket reflects the light, thereby increasing the light absorption capacity of the conductive glass. The present invention provides a method for preparing a conductive glass and the conductive glass, which can be applied to the field of optoelectronics, especially the field of solar cells, to enhance their light absorption capacity and improve their photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the prior art and the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 A schematic flow chart of a method for preparing conductive glass provided by the present invention;
[0035] Figure 2 A schematic diagram of the structure of the glass in S1 of the preparation method provided by the present invention;
[0036] Figure 3 This is a schematic structural diagram of a glass substrate after being punched in S1 of the preparation method provided by the present invention;
[0037] Figure 4 This is a schematic diagram of the structure after the first coating is prepared in S2 of the preparation method provided by the present invention;
[0038] Figure 5 This is a schematic diagram of the structure after silicon dioxide is filled in S3 of the preparation method provided by the present invention;
[0039] Figure 6 This is a schematic diagram of the structure after the second coating is prepared in S5 of the preparation method provided by the present invention;
[0040] Figure 7 This is a schematic diagram of the structure after perforation in S6 of the preparation method provided by the present invention;
[0041] Figure 8 This is a schematic diagram of the structure of the compound in S7 after sublimation in the preparation method provided by the present invention;
[0042] Fig. 9 This is a schematic diagram of the structure after preparing the third coating in S8 of the preparation method provided by the present invention. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] like Figure 1-Figure 9 As shown, the present invention provides a method for preparing a conductive glass, which may specifically include the following steps:
[0045] S1, drilling holes on the surface of glass 1 so that a plurality of hole-shaped grooves 2 are distributed on the surface to obtain a glass substrate;
[0046] S2, preparing a first coating 3 on the glass substrate so that the first coating 3 covers the surface of the hole-shaped groove 2,
[0047] S3, filling the porous groove 2 with silicon dioxide, wherein the surface of the silicon dioxide after filling is lower than or equal to the height of the hole mouth of the porous groove 2;
[0048] S4, using a plasma etching process to react the filled silicon dioxide to generate a sublimable compound;
[0049] S5, continuing to prepare a second coating 4 on the surface thereof to cover the surface of the filled silicon dioxide and the first coating 3;
[0050] S6, perforating the second coating 4 at the hole-shaped groove 2, wherein the aperture of the perforation 5 is 10-20 nm;
[0051] S7, sublimating the compound in the porous groove 2 by radiation heating, and discharging the compound through the perforation 5;
[0052] S8, continuing to prepare a third coating 6 on the surface thereof to cover the surface of the second coating 4 and seal the perforation 5;
[0053] Thus, conductive glass having air pockets 7 of regular shape can be obtained.
[0054] Specifically, in S1 , glass 1 may be oxide glass or non-oxide glass, wherein oxide glass includes silicate glass, borate glass, phosphate glass, and the like.
[0055] When drilling holes in the glass 1, laser drilling, chemical etching or laser-induced micro-hole deep etching and other processes can be used. Among them, laser drilling is: using laser equipment to scan and irradiate the glass surface according to a predetermined pattern and parameters. The laser can instantly heat and vaporize the glass material, thereby forming tiny holes on the surface; or laser-induced denaturation technology can be used to generate continuous denaturation zones on the glass through picosecond pulse lasers. These denaturation zones will be preferentially removed in the subsequent etching process to form deep holes; or Femto femtosecond laser ultrafast pulse lasers are used to induce glass to generate denaturation zones. This area is more easily etched by hydrofluoric acid. Based on this phenomenon, through holes or blind holes can be made on the glass.
[0056] In a specific embodiment, the porous grooves 2 are arranged in a uniform array. Optionally, the depth of the porous grooves 2 is 1-30 μm, the diameter of the porous grooves is 0.2-20 μm, and the spacing between adjacent porous grooves is 5-100 μm. Optionally, the interior of the porous grooves 2 is a cylindrical hole, and the bottom end surface of the porous grooves 2 is an arc shape, so that the air cavity 7 finally formed is a cylindrical shape with an arc bottom surface, which is conducive to the reflection and absorption of light. Of course, those skilled in the art can also select the size, shape, arrangement, spacing, etc. of the porous grooves 2 according to actual needs, which is not limited here.
[0057] Optionally, after S1 and before S2, the glass substrate may be cleaned to ensure the coating quality.
[0058] In S2, S5 and S8, a coating is prepared on the surface of the glass substrate, wherein the first coating 3, the second coating 4 and the third coating 5 can be the same coating film or coating films of different materials. A conductive coating is usually selected. For example, one or more combinations of coating films such as indium tin oxide (ITO), fluorine-doped tin oxide (FTO), indium zinc oxide (IZO), tin oxide (SnO2), indium oxide (In2O3), metal films, conductive polymers, etc. can be used.
[0059] In a specific embodiment, taking a transparent conductive oxide coating (TCO) as an example, the first coating 3, the second coating 4 and the third coating 5 are all transparent conductive oxide coating (TCO) films. When preparing the first coating 3, the second coating 4 and the third coating 5, physical vapor deposition (PVD) or chemical vapor deposition (CVD) methods can be used.
[0060] Taking the physical vapor deposition method as an example, the following steps are included:
[0061] Cleaning treatment: First, the glass substrate to be electroplated needs to be thoroughly cleaned to remove impurities, grease and oxides on the surface of the glass substrate to ensure that the surface of the glass substrate is smooth and clean.
[0062] Pretreatment: The cleaned glass substrate needs to be pretreated to improve the adhesion and uniformity of the electroplated film. Common pretreatment methods include mechanical grinding, chemical etching, laser processing, etc.
[0063] Evaporation source loading: In the PVD electroplating process, an evaporation source is required to provide material atoms. Evaporation source loading is to place the material evaporation source in a specific position, evaporate it by heating, and accumulate the evaporated metal atoms on the surface of the glass substrate to form a thin film.
[0064] Pulsed magnetron sputtering: High-energy ions generated by cathode ion bombardment cause the evaporated material to dissociate from the evaporation source and deposit on the surface of the glass substrate in a pulsed manner.
[0065] Post-processing: After PVD electroplating is completed, post-processing is required, including surface polishing, cleaning and protection steps to remove surface impurities and improve film performance.
[0066] Optionally, the thickness of the first coating layer 3 is less than half the diameter of the pore-shaped groove 2. Preferably, the thickness of the first coating layer is 30-150 nm. Figure 3 As shown, after the first coating 3 is prepared, the first coating 3 covers the surface of the glass substrate and the hole-shaped groove 2, and there is still a groove in the hole-shaped groove 2, so as to facilitate the next step of filling the groove with silicon dioxide. Of course, those skilled in the art can also select the thickness of the first coating 3 according to actual needs, which is not limited here.
[0067] like Figure 5 As shown, in S3, silicon dioxide is filled in the porous groove 2, and the surface of the silicon dioxide after filling is lower than or equal to the hole height of the porous groove 2. Optionally, filling silicon dioxide specifically includes the following steps: 1. Primary filling: filling the porous groove with a first dose of silicon dioxide; 2. High temperature densification: densification at a temperature of 900 to 1100°C for 5-10 minutes; 3. Secondary filling: filling the porous groove with a second dose of silicon dioxide. The ratio of the first dose to the second dose is 1:0.4 to 0.6.
[0068] Specifically, during the primary filling, a first dose of silicon dioxide is filled into the porous groove 2 to cover the bottom and side walls of the porous groove 2, but it is not enough to fill the porous groove 2. During high-temperature densification, temperature: the temperature of high-temperature densification is 900-1100°C. Time: the time of high-temperature densification is 5-10 minutes. Specific process: the glass substrate that has completed the primary filling is heated in a furnace tube. Secondary filling: the second dose of silicon dioxide is filled into the deep groove until the surface of the silicon dioxide is lower than or equal to the hole mouth height of the porous groove 2. By adding a high-temperature densification step between the first filling and the second filling, it helps to eliminate dislocation defects.
[0069] It should be understood that those skilled in the art may also use other methods to fill silicon dioxide, such as spin coating, etc., which are not limited here.
[0070] In S4, the filled silicon dioxide is reacted to generate a sublimable compound by a plasma etching process. The plasma etching process used is a Siconi process, which specifically includes the following steps:
[0071] Placing a glass substrate in a SiCoNi process chamber;
[0072] An etching gas is introduced into the process chamber, wherein the etching gas is a mixed gas of nitrogen trifluoride (NF3) and ammonia (NH3).
[0073] The etching gas generates remote plasma under the action of the radio frequency system, reacts with SiO2 to generate the easily sublimable compound (NH4)2SiF6.
[0074] It should be understood that the glass substrate has been covered by the first coating 3 in step S2, thereby preventing the silicon dioxide on the glass substrate from reacting with the active particles generated by the mixed gas of NF3 and NH3 under the action of plasma. In addition, in order to prevent the silicon dioxide on the glass substrate from participating in the reaction, the side or bottom of the glass substrate may be coated, or the glass substrate may be placed in a groove of the same size and shape as the glass substrate in the SiCoNi process chamber to prevent the silicon dioxide on the side or bottom from being irradiated by the plasma.
[0075] like Figure 6 As shown, in step S5, a second coating 4 is further prepared on the surface to cover the surface of the filled silicon dioxide and the first coating 3. The second coating 4 can be a conductive coating film, which can be the same material or a different material as the first coating 3, as long as it is a material that can transmit light.
[0076] The preparation method of the second coating layer 4 is the same as that of the first coating layer 3, and will not be described in detail here.
[0077] like Figure 7As shown, in step S6, the second coating 4 at the hole-shaped groove 2 is perforated. The aperture size of the perforation 5 is limited to be used for the compound (NH4)2SiF6 to be discharged from the perforation 5 when it is sublimated, and the perforation 5 cannot be too large. If the aperture of the perforation 5 is too large, the third coating 6 is easily deposited into the air cavity 7 when the third coating 6 is prepared, which has an adverse effect on the shape and size of the air cavity 7. If the aperture of the perforation 5 is too small, the sublimation of the compound (NH4)2SiF6 will be slow, or it will be difficult to be discharged from the perforation 5. At the same time, too small an aperture will also lead to too high a precision requirement for the perforation process, and the processing difficulty is greater. Since the molecular diameter of the compound (NH4)2SiF6 is approximately 0.5-1.0nm, the aperture of the perforation 5 needs to be greater than 1nm. Optionally, the aperture of the perforation 5 is 10-20nm. That is, the upper limit of the aperture of the through hole 5 is related to the preparation process of the third coating 6, and the lower limit of the aperture of the through hole 5 is related to the sublimation and discharge of the compound (NH4)2SiF6.
[0078] It should be understood that in the prior art, the Siconi process is often used for pre-cleaning of material surfaces to remove the natural oxide layer and other contaminants on the surface of silicon wafers, providing a clean surface for subsequent epitaxial growth or other process steps. In the present invention, the inventor innovatively combines it with the micropore process, which can react with the silicon dioxide in the pore-shaped grooves below the micropores to remove the silicon dioxide in the pore-shaped grooves below the micropores, and then combines the coating preparation process to cover the micropores, thereby forming cavitations with regular and controllable shapes.
[0079] Optionally, in S6, micro-nano processing technology is used for perforation. Micro-nano processing technology is any one of electron beam exposure, focused ion beam or nanoimprinting process. Electron beam exposure (Electron Beam Lithography, EBL) is a technology that uses a focused electron beam to directly "draw" nanoscale patterns on electron-sensitive materials, which can be used to manufacture nanoscale holes and structures. Focused ion beam (Focused Ion Beam, FIB) technology can be used for nanoscale cutting and drilling. By precisely controlling the energy and scanning path of the ion beam, nanoscale holes can be engraved on the surface of the material. Nanoimprint Lithography (NIL) is a technology for manufacturing large-area nanostructures, which copies the nanostructure on the mold to the substrate by imprinting. These processes can all perforate the second coating 4 at the hole-shaped groove 2, and the size of the perforation is on the order of tens of nanometers.
[0080] like Figure 8As shown, in S7, the compound in the porous groove 2 is sublimated by radiation heating and discharged through the perforation 5. Specifically, the temperature of the radiation heating is 170-190° C. Preferably, the temperature of the radiation heating is 180° C. The compound (NH4)2SiF6 in the porous groove 2 can be removed by the sublimation process of S7.
[0081] like Fig. 9 As shown, in S8, the third coating 6 is continuously prepared on the surface thereof to cover the surface of the second coating 4 and block the through-hole 5. Since the aperture size of the through-hole 5 is particularly limited, when the third coating 6 is prepared, the atoms of the third coating 6 are deposited in the hole of the through-hole 5 during deposition, so that the aperture of the through-hole 5 gradually becomes smaller and is finally blocked.
[0082] Optionally, the third coating 6 can be a conductive coating film, which can be the same material or different material as the first coating 3, as long as it is a material that can transmit light. The preparation method of the second coating 4 can also be the same as or different from that of the first coating 3. Preferably, the third coating 6 is prepared by a physical vapor deposition (PVD) process, which can better block the perforation 5 and prevent the atoms of the third coating 6 from entering the air cavity 7.
[0083] The present invention provides a method for preparing a conductive glass, wherein the conductive glass prepared by the method has regularly shaped air pockets 7 in its coating, and the position, shape, size, arrangement and distribution of the air pockets 7 can be controlled by the process.
[0084] Comparative Example:
[0085] The glass substrate was cleaned with a cleaning agent, tap water and ultrapure water in sequence, and then dried; a mixed solution for preparing FTO was prepared, and SnCl4, methanol and hydrochloric acid were used for reaction; according to SnCl4·5H2O and NH4F accounting for 4.8wt%, methanol and water were added to a solvent with a ratio of 5.5:1, wherein SnCl4·5H2O and the solvent were diluted at a ratio of 5ml per 1g; an FTO film was prepared by a thermal spraying film-forming device; the thickness of the FTO film was 500nm.
[0086] Experimental Example 1:
[0087] The glass surface is perforated, the depth of the hole-shaped groove is 10 μm, the diameter of the hole-shaped groove is 3 μm, and the spacing between adjacent hole-shaped grooves is 20 μm; then the glass substrate is cleaned with a cleaning agent, tap water, and ultrapure water in turn, and the glass substrate is dried after cleaning; a first coating FTO film with a thickness of 100 nm is prepared by a thermal spraying film-forming process; silicon dioxide is filled; the glass substrate is placed in a SiCoNi process chamber, and remote plasma etching is performed to make the filled silicon dioxide react to generate a sublimable compound (NH4)2SiF6; a second coating FTO film with a thickness of 200 nm is prepared by a thermal spraying film-forming process; an electron beam exposure process is used to perforate the second coating 4 at the hole-shaped groove. The aperture of the perforation 5 is 10 nm; the compound in the hole-shaped groove 2 is sublimated by radiation heating and discharged through the perforation 5; and a third coating FTO film with a thickness of 200 nm is prepared by a thermal spraying film-forming process.
[0088] Experimental Example 2:
[0089] The glass surface is perforated, the depth of the hole-shaped groove is 15 μm, the diameter of the hole-shaped groove is 8 μm, and the spacing between adjacent hole-shaped grooves is 30 μm; then the glass substrate is cleaned with a cleaning agent, tap water, and ultrapure water in turn, and the glass substrate is dried after cleaning; a first coating FTO film with a thickness of 150 nm is prepared by a thermal spraying film-forming process; silicon dioxide is filled; the glass substrate is placed in a SiCoNi process chamber, and remote plasma etching is performed to make the filled silicon dioxide react to generate a sublimable compound (NH4)2SiF6; a second coating FTO film with a thickness of 150 nm is prepared by a thermal spraying film-forming process; an electron beam exposure process is used to perforate the second coating 4 at the hole-shaped groove. The aperture of the perforation 5 is 15 nm; the compound in the hole-shaped groove 2 is sublimated by radiation heating and discharged through the perforation 5; and a third coating FTO film with a thickness of 200 nm is prepared by a thermal spraying film-forming process.
[0090] Experimental Example 3:
[0091] The glass surface is perforated, the depth of the hole-shaped groove is 20 μm, the diameter of the hole-shaped groove is 10 μm, and the spacing between adjacent hole-shaped grooves is 50 μm; then the glass substrate is cleaned with a cleaning agent, tap water, and ultrapure water in turn, and the glass substrate is dried after cleaning; a first coating FTO film with a thickness of 100 nm is prepared by a thermal spraying film-forming process; silicon dioxide is filled; the glass substrate is placed in a SiCoNi process chamber, and remote plasma etching is performed to make the filled silicon dioxide react to generate a sublimable compound (NH4)2SiF6; a second coating FTO film with a thickness of 100 nm is prepared by a thermal spraying film-forming process; an electron beam exposure process is used to perforate the second coating 4 at the hole-shaped groove. The aperture of the perforation 5 is 15 nm; the compound in the hole-shaped groove 2 is sublimated by radiation heating and discharged through the perforation 5; and a third coating FTO film with a thickness of 100 nm is prepared by a thermal spraying film-forming process.
[0092] Table 1. Comparison of conductivity and light transmittance between comparative examples and experimental examples
[0093]
[0094]
[0095] It can be seen from Table 1 that the comparative example only includes TCO film, and its total light transmittance is 80%, while in the TCO films of Experimental Examples 1-3, air holes of different densities are prepared. From the test results, it can be seen that the difference in their conductive properties (surface resistance, resistivity) is small, while the total light transmittance is significantly reduced, which shows that the light absorption capacity of the conductive glass is significantly increased.
[0096] The present invention also provides a conductive glass, which is made by the above-mentioned preparation method and has a plurality of regularly shaped air holes 7 in the coating on its surface.
[0097] Preferably, the coating used on the surface of the conductive glass is a transparent conductive oxide coating, which has excellent photoelectric properties such as wide band gap, low resistivity, high light transmittance in the visible light region and high light reflectivity in the infrared spectrum region. In the present invention, by preparing air pockets 7 with regular shapes and uniform and controllable sizes in the conductive coating of the glass substrate, when light passes through the conductive coating, the inner wall of the air pocket 7 will reflect the light, thereby increasing the light absorption capacity of the conductive glass.
[0098] The present invention provides a method for preparing a conductive glass and the conductive glass, which can be applied to the optoelectronic field, especially the solar cell field, to enhance the light absorption capacity and improve the photoelectric conversion efficiency.
[0099] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the embodiments described. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the embodiments described.
Claims
1. A method for preparing conductive glass, characterized in that: The following steps are involved: S1, drilling holes on the surface of the glass so that a plurality of hole-shaped grooves are distributed on the surface to obtain a glass substrate; S2, preparing a first coating on the glass substrate so that the first coating covers the surface of the hole-shaped groove, S3, filling the porous groove with silicon dioxide, wherein the surface of the silicon dioxide after filling is lower than or equal to the hole height of the porous groove; S4, using a plasma etching process to react the filled silicon dioxide to generate a sublimable compound; S5, continuing to prepare a second coating on the surface thereof to cover the surface of the filled silicon dioxide and the first coating; S6, perforating the second coating layer at the hole-shaped groove, wherein the aperture of the perforation is 10-20 nm; S7, sublimating the compound in the porous groove by radiant heating and discharging the compound through the perforation, S8, continuing to prepare a third coating on the surface thereof to cover the surface of the second coating and seal the perforation; Conductive glass with regularly shaped air pockets can be obtained.
2. The method for preparing conductive glass according to claim 1, characterized in that: In S1, the surface of the glass is perforated by laser drilling, chemical etching or laser-induced micropore deep etching process.
3. The method for preparing conductive glass according to claim 1, characterized in that: In S1, the hole-shaped grooves are arranged in a uniform array, the depth of the hole-shaped grooves is 1-30 μm, the diameter of the hole-shaped grooves is 0.2-20 μm, and the spacing between adjacent hole-shaped grooves is 5-100 μm.
4. The method for preparing conductive glass according to claim 1, characterized in that: The first coating layer, the second coating layer and the third coating layer are all transparent conductive oxide coating layers; When preparing the first coating, the second coating and the third coating, a physical vapor deposition method or a chemical vapor deposition method is adopted; The transparent conductive oxide coating is referred to as a TCO film.
5. The method for preparing conductive glass according to claim 1, characterized in that: The thickness of the first coating layer is less than half of the diameter of the hole-shaped groove.
6. The method for preparing conductive glass according to claim 1, characterized in that: The thickness of the first coating layer is 30-150 nm.
7. The method for preparing conductive glass according to claim 1, characterized in that: In S3, filling with silicon dioxide specifically includes the following steps: Primary filling: Fill the first dose of silicon dioxide into the porous groove. High temperature densification: densification is carried out at a temperature of 900-1100°C for 5-10 minutes. Secondary filling: filling the hole-shaped groove with a second dose of silicon dioxide; Among them, the ratio of the first dose to the second dose is 1:0.4~0.
6.
8. The method for preparing conductive glass according to claim 1, characterized in that: In S4, the plasma etching process is a Siconi process, which includes the following steps: Placing a glass substrate in a SiCoNi process chamber; Introducing an etching gas into the process chamber, wherein the etching gas is a mixed gas of nitrogen trifluoride and ammonia; The etching gas generates remote plasma under the action of the radio frequency system, reacts with silicon dioxide to generate a compound that is easily sublimated; In S7, the temperature of the radiation heating is 170-190°C.
9. The method for preparing conductive glass according to claim 1, characterized in that: In S6, micro-nano processing technology is used for perforation, and the micro-nano processing technology is any one of electron beam exposure, focused ion beam or nanoimprinting process.
10. A conductive glass, characterized in that: The coating is prepared by the preparation method described in any one of claims 1 to 9, and has a plurality of regularly shaped air pockets in the coating on its surface.